STUDI LITERATUR : MODEL PEMBELAJARAN KOOPERATIF LEARNING THINK PAIR SHARE DAN HASIL PASSING CONTROL SEPAKBOLA. - Rahmad Khoirudin; Ratno Susanto; Achmad Afandi (Cahaya Ilmu Bangsa Institute, 2023)
Cooperative learning method Learning Think Pair Share is a learning method designed to invite students to seek answers to a question from a concept through a group. The Think Pair Share learning method was introduced by Frank Lyman with the aim that discussions have various variations that are not monotonous and can develop to be more creative. This learning model requires students to think independently about the topic or question given. Passing is one of the techniques of passing the ball to a friend or team and control is one of the movements to receive the ball from friends or teams, in football it has many basic techniques such as passing, control, shooting, heading, and dribbling. In football, it is a mission to enter the ball into the enemy's goal as much as possible so as to win a match